Status of digital heritage preservation management in Eastern Africa. Issue 3 (27th May 2014) - Mudogo Mutula, Stephen
Abstract : Purpose: – The primary purpose of this paper was to assess the status of digital heritage preservation management in Eastern Africa. The following research objectives were addressed: investigate digital heritage preservation management in Eastern Africa, find out the content which is prioritized for digital preservation, describe the challenges of digital heritage preservation management in Eastern Africa and propose a framework to address challenges of digital heritage preservation in Eastern Africa. Design/methodology/approach: – This paper is based on a literature review and an analysis of national digitization efforts in Eastern Africa. The research objectives were addressed using Document Lifecycle and World Summit on Information Society Action Lines 2, 3 and 8 as the theoretical frames. Findings: – Results revealed growing awareness among institutions with statutory responsibility for heritage management about digital heritage preservation in Eastern Africa through the support of international agencies, civil societies and governments. However, institutions with responsibility for heritage management were ill-equipped to function in this role effectively. Content of academic, commercial, parliamentary and judicial and international treaties' values were the preferred candidates for digitization. The findings revealed several challenges hampering digital heritage preservation management: weak policy and regulatory frameworks, limited capacity, inadequate government support and limited connectivity and bandwidth. Originality/value: – Many countries in Eastern Africa are making efforts to preserve their national heritage through digitalization to bridge the content divide between the region and the developed world so as to enhance access by its people, not only to their respective national heritages but also for international information systems knowledge. However, most of these efforts remain undocumented, making it difficult to make comparisons with similar best practices around the world.